FAKTOR MINAT BERDONASI PADA LEMBAGA AMIL ZAKAT SAHABAT MUSTAHIQ - Ricky Nuari; Achsania Hendratmi (Universitas Airlangga, 2019)
The lack of information in understanding the factors of donors' interest in donating to charitable institutions is the reason for the lack of optimization of the collection of donations. This study aims to determine the effect of age, income, education, generosity, financial security and religiosity on the interest in donating to LAZ Sahabat Mustahiq. This study uses a quantitative approach with multiple linear regression analysis methods and data collection by distributing questionnaires to 107 permanent donors, Friends of Mustahiq. The results of this study showed that the independent variables partially showed that interest donors donated at LAZ Sahabat Mustahiq were influenced by religiosity. That is because the majority of the population of Muslim Indonesia adheres to their religion. Factors of age, income, education, financial security, and generosity partially have no effect on interest in donating. While simultaneously all independent variables influence interest in donating.Keywords: Donation, Interest, Factors, Multiple Linear Regression.